1998
DOI: 10.1111/j.1751-0813.1998.tb10126.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of inflammation‐associated acute‐phase response on hepatic and renal indices in the horse

Abstract: The effects of the acute-phase response on indices of hepatic and renal function in the horse suggest that the disposition of pharmacological agents administered at this time may be altered and that indices of acute inflammation should be interpreted cautiously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
1
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 26 publications
3
21
1
3
Order By: Relevance
“…This likely reflects the different duration of inflammation between the two models. Mills et al (1998) administered 2 mL of FCA on the first, second and fifth days of the experiment and, as in our study, observed an increase in edema and temperature at the injection site that reached a maximum at 72 h after the first dose and diminished by half of the maximum on day 12. In our work, localized edema was detected at 6 h PI, but in contrast to the results obtained by Mills et al (1998), the edema began to resolve on the fifth day (M120), after which, it migrated to the pectoral region and completely disappeared at the end of the experiment.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…This likely reflects the different duration of inflammation between the two models. Mills et al (1998) administered 2 mL of FCA on the first, second and fifth days of the experiment and, as in our study, observed an increase in edema and temperature at the injection site that reached a maximum at 72 h after the first dose and diminished by half of the maximum on day 12. In our work, localized edema was detected at 6 h PI, but in contrast to the results obtained by Mills et al (1998), the edema began to resolve on the fifth day (M120), after which, it migrated to the pectoral region and completely disappeared at the end of the experiment.…”
Section: Discussionmentioning
confidence: 62%
“…It is known that hypoferremia can be induced in horses during inflammation, such as after the administration of Freund's complete adjuvant (FCA) (Auer et al 1989, Mills et al 1997, Mills et al 1998) and occurs before elevation in plasma fibrinogen. Therefore, the aim of this study was to evaluate the clinical findings and hepcidin gene expression in the livers of healthy horses using an FCA model of inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…In horses, increased Hp serum or plasma concentration has been observed following surgery [90,171], experimental inflammations [45,80,113,171] as well as during natural diseases [90,114,171] (Tab. IV).…”
Section: Equine Haptoglobinmentioning
confidence: 99%
“…Banding is not associated with changes in the Hp concentration [41], whereas castration is followed by an increased Hp level Cattle Experimental local aseptic inflammation [22,28] Infection with bovine virus diarrhea virus and Pasteurella haemolytica [61] Experimental infection with P. multocida [33] Experimental infection with P. haemolytica [87] Infection with bovine herpes virus 1 and P. haemolytica A1 [58] Experimental infection with bovine respiratory syncytial virus [65] Natural infections with foot-and-mouth disease virus [81] Mastitis [40,68,70,130,152] Various acute infections under field conditions [164] Clinical respiratory tract disease [188] Various inflammatory diseases [6] Acute inflammations [104] Castration [35,47,50,51,52] Ruminotomy [119] Metritis [71,165,166] Severe uterine bacterial post partum contamination [160] Fatty liver (hepatic lipidosis) [87,124,192] Nonfeeding for 3 days [88] Starvation for 2 days combined with Dexamethasone treatments [193] Transportation for 2 days [120] Major injuries at slaughter/culling [69,149] Horse Experimental aseptic arthritis [80] Experimental local aseptic inflammation [113,171] Experimentally induced noninfectious ...…”
Section: Bovine Haptoglobinmentioning
confidence: 99%
“…Auch das Endokrinium ist von den Verän-derungen während der APR betroffen. Erkrankte und verletzte Individuen haben gesteigerte Plasmakonzentrationen von Hormonen, darunter Glukagon, Insulin, ACTH, Kortisol, Katecholamine, Thyreotropes Hormon (TSH), Thyroxin, Aldosteron und Vasopressin (Kushner 1982, Mills et al 1997, Mills et al 1998. Die Zytokine Interleukin-6 (IL-6), Tumor Nekrose Faktor-α (TNF-α) und Interleukin-1 (IL-1) steigern die Prostaglandin-E 2 -Synthese, woraus die Erhöhung der Körperinnentempe-ratur resultiert (Morris et al 1992).…”
unclassified